CAN DIGITAL LITERACY PRACTICES MOTIVATE INTERNATIONAL STUDENTS TO UPGRADE THEIR ENGLISH AS A SECOND LANGUAGE (L2)?: AN ETHNOGRAPHY CASE STUDY - Tri Febrianti Valentina; Yudhi Arifani; Khoirul Anwar (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2021)
This article discussed how to bridge communication between international students studying at host universities in other countries through digital literacy practices and is a model for global social interaction. This article also investigates the use of English proficiency, specifically for students in Indonesia and Thailand via online platform. It is based on semi structure interviews synchronously and asynchronously conducted with international students in both countries. The article focuses on five international students studying abroad from five different countries. This article uses an ethnography case study which describes some images from the results and findings in greater depth. The findings indicate the reasons for analysis and effectiveness in moving literacy practice toward digitalization for L2 students. These findings suggest that new literacy learning is rapidly evolving with advanced technology, necessitating the use of a high-speed Internet connection. This study contributes to language planning as L2 based on ethnography which has also been adapted into digital literacy for Thai and Indonesian students. In addition, this research's contribution is to give some people more about the importance of digital literacy practices, especially for an institution that has international students in teaching and learning. The authors' focus is on their personal experiences with digital literacy practices